2005
DOI: 10.1016/j.joca.2005.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of IL-1β and hydrogen peroxide (H2O2) on catabolic and anabolic gene expression in juvenile bovine chondrocytes

Abstract: The different regulation of NF-kappaB and AP-1 by H(2)O(2) and IL-1beta underlines the distinct roles played by the two transcription factors in the regulation of gene expression. H(2)O(2) and IL-1beta exert similar effects on matrix, MMPs and TGF-beta1 gene expression. However, the association of H(2)O(2) and IL-1beta does not cause synergic effect, and rather leads, in some cases, to an opposite effect. These data provide further insights into the respective roles of reactive oxygen species and cytokine in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
5
25
1
Order By: Relevance
“…22 Treatment of chondrocytes with 50-100 μM H 2 O 2 for one day was reported to induce the transcription factor activator protein 1 and to up-regulate matrix metalloproteinase 3 expression. 23 We showed the up-regulated metalloproteinase mechanism for ADAMTS9 expression at a higher concentration of H 2 O 2 in this study.…”
supporting
confidence: 59%
“…22 Treatment of chondrocytes with 50-100 μM H 2 O 2 for one day was reported to induce the transcription factor activator protein 1 and to up-regulate matrix metalloproteinase 3 expression. 23 We showed the up-regulated metalloproteinase mechanism for ADAMTS9 expression at a higher concentration of H 2 O 2 in this study.…”
supporting
confidence: 59%
“…It has been also demonstrated that IL-1b and hydrogen peroxide caused the activation of the redox-dependent transcription of NF-κB and AP-1 in bovine chondrocytes [45]. This effect triggers a remarkable decrease in type II collagen transcription, associated with a significant increase in MMP synthesis [45], leading to the onset of cartilage structural damage.…”
Section: Discussionmentioning
confidence: 95%
“…This effect triggers a remarkable decrease in type II collagen transcription, associated with a significant increase in MMP synthesis [45], leading to the onset of cartilage structural damage. Moreover, Terkeltaub et al [46] showed that IL-1β and TNFα induced the expression of important metalloproteinases, such as MMP-3 and MMP-13.…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations, reactive oxygen species downregulate chondrocyte responses to proinflammatory cytokines 39 . However, at higher concentrations, reactive oxygen species directly damage the cartilage extracellular matrix, activate matrix metalloproteinases, suppress extracellular matrix synthesis, and induce matrix metalloproteinase expression through activation of the transcription factors activator protein 1 and nuclear factor kappaB 37,40,41 . In addition, concomitant exposure to nitric oxide and to the superoxide radical contributes to chondrocyte apoptosis 18,37 .…”
Section: Discussionmentioning
confidence: 99%